2022
DOI: 10.36987/jes.v9i3.3461
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kemampuan Pemahaman Konsep Matematika Menggunakan Model Problem Based Learning Pada Materi Pola Bilangan Di Kelas Viii SMP Negeri 3 Wertamrian Kabupaten Kepulauan Tanimbar

Abstract: This study aims to determine the learning design of speech pattern material for class VIII students of SMP Negeri 3 Wertamrrian using a problem based learning model and determine students' ability to understand mathematical concepts through number patterns after using a problem-based learning model for class VIII students of SMP Negeri 3 Wertamrrian. This research was conducted at SMP Negeri 3 Wertamrian, Tanimbar Islands Regency in November 2022. This type of research is a qualitative research using a researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Each mathematical ability has its own indicator which is used as a reference in research, while the indicators of repetition ability according to NCTM (2003, 2) are as follows: 1) use of repetition to model and intellectual interpretation of physical, social, and mathematical phenomena, 2) creative and use reipretation to organize, record, and communicate mathematical ideas, and 3) select, apply, and translate to slovei problems. From the explanation above, it can be explained that indicators of mathematical representation ability include 1) using representation (veirbal, symbolic and visual) to model and interpret physical, social, and mathematical phenomena, 2) creating and using verbal, symbolic and visual representations) to remember to communicate mathematical ideas and, 3) choosing to apply and translate mathematical representations (veirbal, symbolic and visual) to solve problems (Ratuanik, Mesak;Lolonlun,Blasius;Bacori, 2022). Minarni (2016) explained that mathematical representations can be reproduced in visual and non-visual representations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each mathematical ability has its own indicator which is used as a reference in research, while the indicators of repetition ability according to NCTM (2003, 2) are as follows: 1) use of repetition to model and intellectual interpretation of physical, social, and mathematical phenomena, 2) creative and use reipretation to organize, record, and communicate mathematical ideas, and 3) select, apply, and translate to slovei problems. From the explanation above, it can be explained that indicators of mathematical representation ability include 1) using representation (veirbal, symbolic and visual) to model and interpret physical, social, and mathematical phenomena, 2) creating and using verbal, symbolic and visual representations) to remember to communicate mathematical ideas and, 3) choosing to apply and translate mathematical representations (veirbal, symbolic and visual) to solve problems (Ratuanik, Mesak;Lolonlun,Blasius;Bacori, 2022). Minarni (2016) explained that mathematical representations can be reproduced in visual and non-visual representations.…”
Section: Resultsmentioning
confidence: 99%
“…This research type of literature study in this research was conducted to analyze the mathematical representational representation abilities of male and female students in solving different mathematics problems. Data Analysis Techniques The research was carried out using qualitative analysis techniques, namely quoting appropriate opinions (Ratuanik, Mesak;Lolonlun,Blasius;Bacori, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The type of research that the researchers used in this study was an exploratory survey that led to a qualitative approach, Nassaji (2015) who stated that qualitative or descriptive research aims to describe a phenomenon with various characters with its scope. In this study, the researchers focused more on field observation data related to the use of the PMRI approach in the context of the Tanimbar stone-burning culture (Ratuanik, Mesak;Lolonlun,Blasius;Bacori, 2022). The research sample that the researchers used was class VIII SMP Negeri Kormomolin, Kormomolin District, Tanimbar Islands Regency.…”
Section: Methodsmentioning
confidence: 99%
“…The word mathematics describes a broad view of mathematics including computation or solving, arithmetic, classifying, sequencing, decision making and modeling (Ratuanik, Mesak;Lolonlun,Blasius;Bacori, 2022). The definition of Ethnomatematics according to Rosa & Orey, (Jakobus, et al: 2021) "the ethnomatematical practices of indentifiable cultural groups and may be regaaded as studies of mathematical ideas found in any culturewhich" means that "ethnomatematical practices from cultural groups that can be identified and can be arranged redefined as the study of mathematical ideas found in any culture (Matematika et al, 2022).…”
mentioning
confidence: 99%